Quantitative CT assessment of bone mineral density in dogs with hyperadrenocorticism - Lee, Donghoon (J Vet Sci, 2015)
Canine hyperadrenocorticism (HAC) is one of the most common causes of general osteopenia. In this study, quantitative computed tomography (QCT) was used to compare the bone mineral densities (BMD) between 39 normal dogs and 8 dogs with HAC (6 pituitary-dependent hyperadrenocorticism [PDH]; pituitary dependent hyperadrenocorticism, 2 adrenal hyperadrenocorticism [ADH]; adrenal dependent hyperadrenocorticism) diagnosed through hormonal assay. A computed tomogaraphy scan of the 12th thoracic to 7th lumbar vertebra was performed and the region of interest was drawn in each trabecular and cortical bone. Mean Hounsfield unit values were converted to equivalent BMD with bone-density phantom by linear regression analysis. The converted mean trabecular BMDs were significantly lower than those of normal dogs. ADH dogs showed significantly lower BMDs at cortical bone than normal dogs. Mean trabecular BMDs of dogs with PDH using QCT were significantly lower than those of normal dogs, and both mean trabecular and cortical BMDs in dogs with ADH were significantly lower than those of normal dogs. Taken together, these findings indicate that QCT is useful to assess BMD in dogs with HAC.